Application of a preference relationship in decision-making based on intuitionistic fuzzy soft sets - Kilicman, Adem; Khameneh, Azadeh Zahedi; Salleh, Abdul Razak (IOS Press, 2018)
Intuitionistic fuzzy soft set (IFSS) provides more efficient and flexible tool than ordinary fuzzy soft set (FSS) to express decision makers’ opinions in real-world decision problems. Until now, different researchers have designed different algorithms for ranking objects in order to select the best option in group decision-making problems under intuitionistic fuzzy soft environment. In this paper, an adjustable algorithm is developed to handle the problem of group decision-making based on a preference relationship of IFSSs. The effectiveness of this approach in comparison with some existing methods is also demonstrated. To achieve the higher level of compatibility with the real-world problems, the proposed algorithm here is extended to the weighted case.